2017
DOI: 10.24873/j.rpemd.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tobacco use and tobacco cessation counseling by Portuguese dentists

Abstract: a b s t r a c t a r t i c l e i n f oArticle history: Received 29 September 2016Accepted 31 December 2016 Available online 30 March 2017Objectives: This study aimed to assess the tobacco use by Portuguese dentists and their intervention in their patients' tobacco prevention and cessation.Methods: In 2006, a questionnaire was mailed to 5298 Portuguese dentists. This questionnaire focused on their tobacco use habits and their attitude toward tobacco prevention and cessation in their patients. In 2013, a second q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…36,44,50,54,67 Awareness on various forms of tobacco was reported in only 3 studies 18,20,46 and in all 3 studies, the knowledge score was high. Knowledge on NRT/pharmacotherapy was also reported in studies conducted by Yahya NA et al, 50 Resende M et al, 49 Studts JL et al 41 and Saddichha S et al 54 and in majority it was found to be between 50-75%. Figure 3 depicts thirty seven studies 15-18,23-26,28-33,36, 37,39-42,44-46, 48-50,52,55-57,61,64,65,68,70,71 which assessed the attitude of dental professionals towards tobacco cessation counseling.…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…36,44,50,54,67 Awareness on various forms of tobacco was reported in only 3 studies 18,20,46 and in all 3 studies, the knowledge score was high. Knowledge on NRT/pharmacotherapy was also reported in studies conducted by Yahya NA et al, 50 Resende M et al, 49 Studts JL et al 41 and Saddichha S et al 54 and in majority it was found to be between 50-75%. Figure 3 depicts thirty seven studies 15-18,23-26,28-33,36, 37,39-42,44-46, 48-50,52,55-57,61,64,65,68,70,71 which assessed the attitude of dental professionals towards tobacco cessation counseling.…”
mentioning
confidence: 60%
“…All twelve studies 15,21,30,35,36,44,46,49,57,58,68,66 reported that study participants had a formal training in tobacco cessation (Figure 5) and among thirty one 16, 18,19,22,26,28-33,35,37,39, 41,42,44,48,50,52,53,55,56,58,59,61,67,70,66,68,71 studies which assessed barriers related to tobacco cessation interventions (Figure 6), time and training were cited to be the most common barriers.
Figure 5.Heatmap of questions on curriculum on tobacco cessation interventions.
Figure 6.Heatmap of questions on barrier towards tobacco cessation interventions.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations